Uroda [‘beauty’] – semantic development of the word in the Polish language - Matusiak-Kempa, Iza (Papers in Linguistics, 2022)
The article present semantic development of the noun uroda [‘beauty’] in the Polish language. The undertaken analysis is based primarily on definitions excerpted from historical dictionaries of the Polish language and selected dictionaries of contemporary Polish. Tracing its semantic development, an attempt is made to point out linguistic and extra-linguistic factors that influence semantic transformations of the noun, which evolved from the meaning of ‘harvest, crops’ towards determining features related to human body concerning its beauty. The first part of the text shows that semantic development of the noun ‘uroda’ was influenced by its etymological connection with the verb ‘urodzić’ as well as its axiological origin, i.e. the origin in the conceptual field of vital values. The second part of the article follows definitions and contexts in which the noun ‘uroda’ surfaces, from occurrences in 16th-century texts to definitions and contexts noted in the era of modern Polish. Analysis of dictionary definitions allows one to believe that the meaning of the noun continues to narrow down, as evidenced by those of its contemporary applications in which it refers to facial attributes.